Nesting and natural history of the Chestnut-bellied Euphonia (Euphonia pectoralis) in Misiones, Argentina, and comparison with other species in the genus - Di Sallo, Facundo Gabriel (2019)
The genus Euphonia includes 28 species that present high levels of specialization on a frugivorous diet, with emphasis on the consumption of mistletoes of the order Santalales. For the Chestnut-bellied Euphonia (Euphonia pectoralis), endemic to the Atlantic Forest of South America, nests and eggs have been described, but other aspects of natural history and reproductive biology are unknown. Here we report observations on foraging and ten reproductive events in eight nests between 2003 and 2018 in Misiones, Argentina. We observed a primarily frugivorous diet in adults and nestlings, although adults occasionally consumed insects when they foraged in mixed species flocks. In contrast to other species of Euphonia, we observed low frequencies of consumption of Santalales fruits. Nests were globular structures of plant material, supported on epiphytic plants, tree trunks, tree ferns, or thin branches 0.93–5.30 m above the ground. Clutch size was 2–3 eggs (n = 6), smaller than for species of Euphonia inhabiting tropical regions, supporting the idea that this genus departs from the general pattern in birds, in which clutch size increases with latitude. The incubation period lasted 16 days and the nestlings fledged when 17–21 days old (n = 2). Both parents participated in nest construction but only the female incubated, brooded, and took care of nest hygiene, ingesting the gelatinous fecal mass directly from the cloaca of her offspring. We observed the male (once) and the female (eight times) feeding the nestlings with regurgitated fruit. Future studies on nesting in the genus Euphonia could help to understand evolution of nesting behaviors in the family, resolve its complex phylogenetic situation, and test hypotheses about the factors influencing clutch size in birds.